Analisa Perbaikan Fasilitas Kerja Operator Mesin Sanding dengan Metode BRIEF Survey dan PLIBEL Checklist untuk Meminimalkan Musculosceletal Disorders (Studi Kasus Pada KMH Co.Ltd) - Muhammad Dwie Ardhieka; Mohammad Riza Radyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In the production process at KMH Co. Ltd. there are still many activities that are not ergonomic and which can repeatedly cause the risk of MSDs complaints and fatigue caused by work facilities that do not meet standards. This research uses quantitative data obtained from observations. The methods used are BRIEF Survey and PLIBEL Checklist. Starting with filling out the Nordic Body Map Questionnaire with the results of operator 2 having the highest score of 70. The results obtained by the BRIEF Survey factor were 2.8% for operator 2, while with an assessment using the PLIBEL Checklist it was obtained that 2 body parts were at risk of developing MSDs in the third operator on the sanding machine, namely the legs for operators 1 and 2 amounted to 92% and 84%, while for operator 3 on the lower back of the bag the figure reached 78%. So as a result of the recapitulation, there needs to be a complete overhaul of the facilities, namely increasing the length of the conveyor from 2m to 4m, increasing the height of the pallet bin from 2cm to 5cm, leaving the machine which previously had no support at a height of around 15cm.